Overview on brain function enhancement of Internet addicts through exercise intervention: Based on reward-execution-decision cycle - Chen, Hao; Dong, Guijun; Li, Kefeng (Frontiers in Psychiatry, 2023)
Internet addiction (IA) has become an impulse control disorder included in the category of psychiatric disorders. The IA trend significantly increased after the outbreak of the new crown epidemic. IA damages some brain functions in humans. Emerging evidence suggests that exercise exerts beneficial effects on the brain function and cognitive level damaged by IA. This work reviews the neurobiological mechanisms of IA and describes the brain function impairment by IA from three systems: reward, execution, and decision-making. Furthermore, we sort out the research related to exercise intervention on IA and its effect on improving brain function. The internal and external factors that produce IA must be considered when summarizing movement interventions from a behavioral perspective. We can design exercise prescriptions based on exercise interests and achieve the goal of quitting IA. This work explores the possible mechanisms of exercise to improve IA through systematic analysis. Furthermore, this work provides research directions for the future targeted design of exercise prescriptions.